Does Nature Determine the Gendered Spaces in Indigenous Society? A Look at the Ivatan Farming System and Food Sovereignty - Dayo, Maria Helen F. (Kasarinlan: Philippine Journal of Third World Studies, 2012)
This study analyzes the paradoxical situation of Ivatan women whose spaces and places are used, valued, and struggled over not only to protect their independent sources of income and livelihood but also to preserve the diversity in local flora and fauna. The paper suggests that it is important to understand their role in household production and reproduction activities as part of their obligation to feed the family. While development policies and programs are geared toward greater participation of indigenous people, the same program fails to contextualize and locate indigenous women whose productive-reproductive roles and worldviews revolve around domestic needs and requirements of the family.
Keywords: Ivatan; gendered spaces; food sovereignty; indigenous peoples; Batanes